Pengaruh Media Tanam Terhadap Pertumbuhan Stek Batang Buah Naga Merah (Hylocereus Polyrhizus) - Umar Husein Abdullah; Intan Riski; Lukman Martunis; Endiyani; Ika Rezvani Aprita; Sri Agustina; Ruhalena Wilis (Jurnal Agrosains dan Teknologi, 2026)
Red dragon fruit (Hylocereus polyrhizus) is a horticultural commodity with high economic value that is generally propagated through stem cuttings. The success of the nursery is greatly influenced by the composition of the planting medium and the balance of growth regulators. This study aims to analyze the effect of various planting medium compositions and the application of bean sprout extract on the growth of red dragon fruit stem cuttings. The study was conducted in Panton Krueng Village, Aceh Jaya, from May to August 2025 using an RBD with four media treatments and six replications. The parameters observed included shoot emergence time, shoot number, and shoot height at 60 dap. The results showed that the soil + sand + compost (1:1:1) medium provided the best response with accelerated shoot emergence (30.2 days), the highest number of shoots, and the highest shoot height (18.6 cm). This combination improves aeration, drainage, and nutrient availability, thus supporting optimal vegetative growth. Shoot growth was strongly positively correlated with the number of shoots, while shoot height was strongly negatively correlated with the time of shoot emergence. These findings indicate that a balanced mixed medium based on organic and mineral materials, along with the application of natural PGRs, has the potential to increase the efficiency and sustainability of the dragon fruit nursery system.